PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KEMAMPUAN BERMAIN TENIS MEJA SISWA KELAS VI SDN 09 RUMBAI PEKANBARU - Nofita Nofita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
The result of fifth grade students’ learning sport from SDN 09 Rumbai Pekanbaru was still low because the method used did not suitable with learning materials. Because of that problem, researcher used direct instructional model in learning table tennis games that could improve the result of fifth grade students’ learning table tennis from SDN 09 Rumbai Pekanbaru. After applying direct instructional model, it could been seen from the teacher’s activity that increased in the first cycle from the first meeting (70%) to the second meeting (75%), and in the second cycle also increased from 85% in the third meeting to 95% in the fourth meeting The students’ activity also increased in the first cycle from 60% in the first meeting to 75% in the second meeting, and in the second cycle also increased from 90% in the third meeting to 95% in the fourth meeting. In the last exam in first cycle average of the students’ learning result increased 2.06 point from based score 69.87 to 72.93. In the last exam in second cycle increased 6.94 point from first cycle to 79.87. From the data analysis, the teacher’s activities, the students’ activities, and the result of students’ learning increased. So, it could be concluded that applying direct instructional model increased the result of fifth grade students’ learning sport from SDN 09 Rumbai Pekanbaru.Key words: direct instructional model, table tennis games